The Effect of Receptie Theory on Legal Concept of “Adat Barenti Lako Syara’, Syara Barenti Lako Kitabullah” - Dianto Dianto (Law Doctoral Program Universitas Muhammadiyah Surakarta, 2020)
Receptie theory of Snouck Hurgonje's thought requires that Islam be valid if it has been perceived by customary law. The perception of a starting point between Islamic law and customary law was mediated by Syahrial Abbas with his split bamboo theory. However, the concept of